2003
DOI: 10.1074/jbc.m303102200
|View full text |Cite
|
Sign up to set email alerts
|

The Glutathione Synthetase of Schizosaccharomyces pombe Is Synthesized as a Homodimer but Retains Full Activity When Present as a Heterotetramer

Abstract: Glutathione synthetase was overexpressed as a histidine-tagged protein in Schizosaccharomyces pombe and purified by two-step affinity chromatography. The recovered enzyme occurred in two different forms: a homodimeric protein consisting of two identical 56-kDa subunits and a heterotetrameric protein composed of two 32-kDa and two 24-kDa subfragments. Both forms are encoded by the GSH2 gene. The 56-Da protein corresponds to the complete GSH2 open reading frame, while the subfragments are produced following the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Glutathione synthesis, catalyzed by the sequential action of ␥-GCS and GS, is nearly ubiquitous in eukaryotes where the tripeptide serves both directly and through enzyme-mediated reactions as an antioxidant and as a sacrificial nucleophile useful in the detoxification of reactive electrophiles (23,27,28). Glutathione synthesis is less common among prokaryotes, but distinct ␥-GCS and GS enzymes have been isolated and characterized from E. coli and several other Gram-negative species (8,19,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione synthesis, catalyzed by the sequential action of ␥-GCS and GS, is nearly ubiquitous in eukaryotes where the tripeptide serves both directly and through enzyme-mediated reactions as an antioxidant and as a sacrificial nucleophile useful in the detoxification of reactive electrophiles (23,27,28). Glutathione synthesis is less common among prokaryotes, but distinct ␥-GCS and GS enzymes have been isolated and characterized from E. coli and several other Gram-negative species (8,19,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…; Phlippen et al . ). In addition to glutathione and phytochelatin, it was previously reported that the glutathione biosynthetic enzymes could also synthesize ophthalmic acid (γ‐glutamyl‐2‐aminobutyrylglycine) in mouse liver and in cyanobacteria (Orlowski & Wilk ; Soga et al .…”
Section: Resultsmentioning
confidence: 97%
“…) and that the Δgsa1 mutant requires glutathione supplementation (Phlippen et al . ). Our Δhmt2 data, however, conflict with a previous report in which the JS563 strain (h + ura4‐294 leu1‐32 Δhmt2 ) grew normally on minimal media.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This might be due to in vivo protein cleavage as it is known that GSH2 in vitro is cleaved into two parts by a metallo-protease between Ala217 and Ser218 [21] and is active as a hetero tetramer as well as in the non-cleaved homodimeric form. Results of another study revealed that this cleavage might have an influence on the differential substrate recognition in the way that the cleaved enzyme accepts Gly only (unpublished data not shown).…”
Section: Resultsmentioning
confidence: 99%